Understanding my disability: exploring how student awareness influences self-advocacy for academic accommodations - Thornton-Savage, Rebekah A. (My University, 2026)
This quantitative quasi-experimental study examined how explicit instruction in disability awareness and IEP literacy influences secondary students’ knowledge of their disability, understanding of accommodations, and self-reported confidence in requesting academic supports within general education settings. Grounded in Self-Determination Theory (Ryan & Deci, 2000), the study explored the relationship between disability awareness, IEP literacy, and students’ perceived readiness to advocate for academic supports among students identified with Specific Learning Disability (SLD), Emotional Disturbance (ED), and Other Health Impairment (OHI). The study was conducted in a rural Kansas high school using a cluster-randomized pretest–posttest control-group design. Students in the experimental group received explicit instruction through Lessons 7–9 of the NEXTUP Transition Curriculum, which focused on understanding disability, identifying accommodations, and developing help-seeking strategies. Quantitative data were collected using lesson-specific pretests and posttests, the Disability Checklist, and the Accommodations and Modifications Awareness Questionnaire. Independent-samples t tests were conducted due to unmatched pretest and posttest samples, and effect sizes (Cohen’s d) were calculated to determine practical significance. Qualitative responses were analyzed using abductive thematic analysis to provide additional context. Findings indicated statistically significant improvements in students’ knowledge of their disability and supports, understanding of accommodations, and self-reported confidence in requesting academic supports following explicit instruction. Large effect sizes suggested meaningful practical impact. Qualitative findings further indicated increased self-awareness, improved understanding of how accommodations support learning, and greater self-reported perceptions of readiness to communicate needs in general education settings. These findings support the integration of explicit IEP-literacy instruction within secondary transition services and highlight the role of structured instruction in promoting student awareness and self-reported perceptions related to self-advocacy. Implications suggest that embedding IEP literacy into existing instructional contexts may strengthen students’ perceived preparedness to advocate for supports, though future research is needed to examine the impact on observed advocacy behaviors over time.
Keywords: Student advocacy; Accommodations; Disability awareness; IEP literacy; Self-advocacy; Self-determination